A new species of Tropidurus (Squamata, Tropiduridae) of the semitaeniatus group from a semiarid area in Northeastern Brazil - Passos, Daniel Cunha; Lima, Daniel Cassiano; Borges-Nojosa, Diva Maria (Zootaxa, 2011)
A new species of Tropidurus of the semitaeniatus group is described from northeastern Brazil. Tropidurus sp. nov. is morphologically similar to other species of the group in the marked dorsoventral flattening of the body, and the presence of a series of sublabial shields that are larger than the adjacent scales. It is distinguished by a single middorsal longitudinal light stripe that extends from the snout to the scapular region. The new species appears to have the largest body size of the group. The new species inhabits the Vale do Jaguaribe, in the eastern part of the state of Ceará, where there are many fissured rocky outcrops surrounded by hypoxerophytic caatinga vegetation.